2010
DOI: 10.1177/112067211002000232
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime Dilution Error

Abstract: Inadvertent intracameral (3 mg in 0.1 mL) cefuroxime injection did not cause any detectable adverse effect on ocular tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 6 publications
0
23
1
3
Order By: Relevance
“…Moreover, the study found that immunoglobulin E-mediated allergy was rare, with 39 reported that the clinically used concentration of cefuroxime seems to be safe to the endothelium. In addition, studies of dosing errors [39][40][41] found that even after a high-dose injection of cefuroxime, the endothelial cell count and retinal function completely recovered after 6 weeks. Delyfer et al 40 found that intracameral injection of very high doses of cefuroxime induced anterior and posterior inflammation (extensive macular edema associated with a large serous retinal detachment and fluorescein angiograms showing diffuse leakage without abnormal retinal perfusion); however, in all cases, the final visual outcome was satisfactory without surgical intervention.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the study found that immunoglobulin E-mediated allergy was rare, with 39 reported that the clinically used concentration of cefuroxime seems to be safe to the endothelium. In addition, studies of dosing errors [39][40][41] found that even after a high-dose injection of cefuroxime, the endothelial cell count and retinal function completely recovered after 6 weeks. Delyfer et al 40 found that intracameral injection of very high doses of cefuroxime induced anterior and posterior inflammation (extensive macular edema associated with a large serous retinal detachment and fluorescein angiograms showing diffuse leakage without abnormal retinal perfusion); however, in all cases, the final visual outcome was satisfactory without surgical intervention.…”
Section: Discussionmentioning
confidence: 95%
“…The macular thickness (mean 288.4 mm G 22.6 [SD]) and profile returned to normal in all patients, although electroretinogaphy recordings showed reduced rod photoreceptor cell function (P!.05). 40 In a study by Sakarya and Sakarya,41 inadvertent intracameral cefuroxime injection (3.0 mg in 0.1 mL) in 6 eyes did not cause a detectable adverse effect on ocular tissues. In our study, 15 of 2289 patients were allergic to beta-lactams.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies of the safety of intracameral cefuroxime have been published. [2][3][4] Our patient received an effective dose of approximately 62.5 mg, which after washout should have been reduced. Intracameral cefuroxime concentration has been shown to decrease to approximately 35% of the initial concentration after 60 minutes.…”
Section: Discussionmentioning
confidence: 97%
“…Minor dilution errors have occurred in the past without incidence. 17 Here, however, we report 6 cases of intraocular inflammation after intracameral injection of a very high dose of cefuroxime secondary to misunderstanding of the dilution protocol at the end of uneventful cataract surgery.…”
mentioning
confidence: 84%